In vivo evaluation of Aloysia triphylla britton (lemon verbena) essential oil toxicity and citral anti-Trypanosma cruzi activity. - Rojas Armas, Juan (2015)
Introduction: There is limited research on neglected diseases. Medicinal plants are potential sources of antimicrobial compounds. Objectives: To determine the toxicity of Aloysia triphylla essential oil and citral activity against Trypanosoma cruzi in mice. Design: Experimental study in vivo, preclinical. Setting: Faculty of Medicine, Universidad Nacional Mayor de San Marcos, Lima, Peru. Biological material: Albino mice. Main outcome measures: Signs of toxicity and mortality and parasitemia. Interventions: Acute oral toxicity at single dose was evaluated in albino rats. For trypanocidal activity mice were assigned to the following groups: untreated infected (G1), infected and treated with citral at doses 50, 150 and 300 mg/kg/day (G2, G3 and G4 respectively), infected and treated with benznidazole 100 mg/kg (G5), and uninfected and untreated (G6). Parasitemia was determined individually every 2 days by direct microscopy. In days 14, 21 and 28 post infection five mice from each group were sacrificed and their hearts processed for histopathology. Results: The limit dose of 2 000 mg/kg did not cause signs or symptoms of toxicity and macro and microscopic anatomopathology did not show alterations in the organs studied. Parasitemia was significantly reduced at dose of 300 mg/kg at days 16, 18, and 20 post infection (p <0.05); the number of amastigote nests and inflammatory infiltrates in heart were reduced on day 28 by 67.7% and 51.7% respectively with 300 mg/kg. Conclusions: Aloysia triphylla essential oil is qualified as nontoxic and citral at 300 mg/kg dose had activity against Trypanosoma cruzi in mice.